صياغة تخريج الحديث المختلف على المدار: Formulating the different interpretations of hadiths based on the syllabus - Lukmanul Hakim Sudahnan (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2026)
This research aims to understand the concept of hadith authentication (takhrij) and its steps, including its formulation according to the established chain of transmission (madhar), as well as the steps for authenticating and formulating variant hadiths according to the established chains of transmission. The research employs an inductive-analytical methodology enriched by practical applications. The findings are as follows: 1- The concept of hadith authentication involves identifying the location of a hadith in its original sources and, when necessary, determining its degree of authenticity. 2- The steps of hadith authentication according to the established chain of transmission involve collecting the various chains of transmission from different sources, identifying the central chain of transmission (madhar) – the narrator at whom the chains converge – determining the type of variation (such as variations between the chain being raised and stopped, or substitution and alteration), counting the number of narrators from each chain of transmission, and authenticating each chain separately as if it were an independent hadith. The steps for formulating the hadith include identifying and stating the central chain of transmission, identifying and explaining the variation and its type, counting the number of narrators from each chain of transmission, and authenticating each chain separately as if it were an independent hadith. 3- The steps for tracing the chain of transmission of a hadith with differing chains of narrators involve gathering the various narrations of the hadith through tracing, updating the chain of transmission of the original hadith (the one closest to the Companion of the Prophet), and identifying the secondary chains of transmission from the original chain. This process also includes determining the type of difference, identifying the number of narrators on the original chain for each version, identifying the secondary chains of transmission from the original chain for each version, and tracing each version separately. The steps for formulating the hadith are the same: updating the chain of transmission of the original hadith (the one closest to the Companion of the Prophet), identifying the secondary chains of transmission from the original chain, determining the type of difference, identifying the number of narrators on the original chain for each version, identifying the secondary chains of transmission from the original chain for each version, and identifying the type of difference within these secondary chains.